2012
DOI: 10.1186/1756-0500-5-645
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the WHO revised criteria for classification of clinical disease severity in acute adult dengue infection

Abstract: BackgroundThe WHO guidelines were revised recently to identify patients with severe dengue (SD) early. We proceeded to determine the usefulness of the warning signs in the new WHO guidelines in predicting SD and we have also attempted to define other simple laboratory parameters that could be useful in predicting SD.MethodsClinical and laboratory parameters were recorded in 184 patients in 2011, with confirmed dengue viral infections, admitted to a medical ward in two tertiary care hospitals in Colombo, Sri La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 27 publications
1
71
1
Order By: Relevance
“…In addition to hypoproteinemia, we found that raised ALT levels were associated with severe form ofdisease. This is in contrast to observations made by Jayaratne et al,stated that raised AST levels were associated with severe dengue and have better predictive value in predicting severe disease [28]. Ours findings indicate that in addition to evaluating hemoconcentration and decreased platelet counts, the presence of low serum protein and raised ALT levels may be taken as a marker for predicting severe disease.…”
Section: Pereira Et Alcontrasting
confidence: 98%
“…In addition to hypoproteinemia, we found that raised ALT levels were associated with severe form ofdisease. This is in contrast to observations made by Jayaratne et al,stated that raised AST levels were associated with severe dengue and have better predictive value in predicting severe disease [28]. Ours findings indicate that in addition to evaluating hemoconcentration and decreased platelet counts, the presence of low serum protein and raised ALT levels may be taken as a marker for predicting severe disease.…”
Section: Pereira Et Alcontrasting
confidence: 98%
“…They are known to play an important role in both acute [11] and chronic viral infections [14,28], including a recent report on their role in dengue infection [12]. Acute dengue is known to associate with a marked lymphopenia [29], especially with reduction of T cells due to massive T cell apoptosis [8,9]. We have also observed that DENV-specific IFN-g T cell responses are impaired during acute dengue, especially in those with more severe forms of dengue [7].…”
Section: Discussionmentioning
confidence: 58%
“…(1) For the prospective studies, the DENCO study provided limited evidence on three warning signs (severe abdominal pain, lethargy, and mucosal bleeding), all predicting severity within 24 hours in advance; 16 also, the combination of five warning signs is a very good predictor of severe disease; 17 2) Retrospective studies on this issue have limited value; 18 however, studies examining the warning signs included the following results: no warning sign alone or combined had a sensitivity of more than 64% in predicting severe disease in one study; 19 however, when warning signs were used for criteria for admission, these were good indicators for severity; 20 ascites, mucosal bleeding, hematemesis, and thrombocytopaenia were identified as good indicators for warning signs; 21 and abdominal pain and hematemesis were identified for the same purpose in another study. 22 The expert panel agreed that D/SD can be used very effectively to identify both pediatric and adult cases of dengue with a risk of progression to shock, specially based on the use of warning signs.…”
Section: Resultsmentioning
confidence: 99%